PENGARUH PRODUK WISATA, DESTINATION IMAGE, DAN WORD OF MOUTH TERHADAP KEPUTUSAN BERKUNJUNG (Studi Kasus pada Pengunjung Objek Wisata Goa Kreo Semarang) - Rizky Priyanto; Widiartanto Widiartanto; Sari Listyorini (Universitas Diponegoro, 2016)
Increased tourism industry make tourist visits in some areas is increasing, its specialty in Central of Java. One of them Attractions is Goa Kreo in Semarang that have unique tourism potential which is inhabited by macaque monkeys. However, the number of tourists from Q1 2014 to Q1 2015 occurred volatile and tend to decline. While the results of pre-research, in getting the dissatisfaction of visitors to the tourism product, in addition to the ideals / image imagined visitors, slightly different from those in Goa Keo. It is fear of the existence of negative information spread among tourists. This study aims to determine the influence of Tourism Products, Destination Image and Word of Mouth to the Decision to Visit Attractions Goa Kreo. This type of research is explanatory research, in which the data collection techniques used is by means of questionnaire, the selected sample of 100 people with accidental sampling and purposive sampling. Respondents are visitor attractions Goa Kreo who've been to Goa Kreo and Goa Kreo find out information from others. The results showed that the Tourism Product and significant effect on Decision to Visit viewed by contributing 18.1% and the rest is explained by other factors. Destination Image influential and significant to the Decision to Visit viewed by contributing 39.1% and the rest is explained by other factors. Word of Mouth influential and significant to the Decision to Visit viewed by contributing 42.6% and the rest is explained by other factors. While, simultaneously Travel Products, Destination Image and Word of Mouth influential and significant to the Decision to Visit. That is, the better the product Tourism, Destination Image and Word of Mouth, make higher the Decision to Visit on Goa Kreo. Additionally Word of Mouth has the most dominant influence to Decision to Visit with regression coefficient of 0.438. The results obtained by analyzing primary data using validity, reliability test, correlation coefficient, determination coefficient, simple linear regression, multiple linear regression, and a significance test (t test and F) with SPSS 20.0. Based on this, the researchers suggested that managers Attractions Goa Kreo further enhance the tourism product, which adds to signpost the way to Goa Kreo, improving tourist attractions, improved facilities and more active in offering a guide to visitors, as well as clarify the job description of employees, thus increasing tourists visit Goa Kreo.